Shared health challenges, political divides: can South Asia heal itself? - Akhtar Sherin (Khyber Medical University Journal)
South Asia, with a population of 2.078 billion people (25.29% of the global population),1 is facing challenges in achieving Sustainable Development Goal (SDG) 3 targets, with most countries scoring around 60% on the SDG 3 index. 2  This region, accounting for a substantial share of global health issues, presents challenges that extend beyond its borders, affecting international health policies and economic stability. The region faces a dual burden of communicable and non-communicable diseases (NCDs). In 2019, it accounted for nearly half of all global cases of drug-susceptible tuberculosis and multidrug-resistant tuberculosis.3 By 2023, India (26%) and Pakistan (6.3%) were among the five countries contributing for 56% of global TB cases. 4 Similarly, NCDs, such as diabetes mellitus, stroke, and heart diseases, are highly prevalent in South Asia, with India and Pakistan among the leading contributors to the global diabetes burden. 5-7 Maternal and child health challenges also persist in South Asia, with only 46% of women receiving comprehensive maternal and neonatal health services, with Afghanistan reporting the lowest coverage at 2.8%.8 Antenatal care utilization remains low, with no significant improvement across SAARC countries from 2015 to 2030.9 The region continues to have one of the highest maternal mortality ratios, with significant disparities; for instance, the Maldives reports high antenatal care utilization (96.83%) compared to Bangladesh (47.01%).10